The othering of majority and minority groups in lessing and Ajidarma’s literary works: a postcolonial analysis - Kurnia, Nandy Intan; Nurgiyantoro, Burhan; Fitri, Cindy Elsa (Penerbit Universiti Kebangsaan Malaysia, 2021)
A postcolonial reading of literary works remains relevant since the characters, stories and various issues related to the colonial domination discussed in literary texts may serve as a means for its readers to learn more about life under colonialism. This article examines how Doris Lessing, a British-Rhodesian author, and Seno Gumira Ajidarma, an Indonesian author, reveal the issue of discrimination of African native community and Indonesian-Chinese community because of the act of othering, respectively, from a postcolonial lens. This study used the critical content analysis technique on two literary works, namely Lessing’s short story entitled “No Witchcraft for Sale” and Ajidarma’s short story entitled “Clara”, which is based on Spivak’s theory of othering. Specific dialogues and utterances related to instances of discrimination were analyzed to uncover the othering of individuals, in this case, the main characters of the stories Lessing’s short story captures the struggles encountered by the main character named Gideon, who belongs to the majority group, while Ajidarma’s short story provides the portrayal of a young native Indonesian-Chinese descent who is a member of a minority group. The study found that Gideon faced racial discrimination and on the other hand, Clara faces racial and gender discrimination. By comparing two different literary works coming from two different cultures, nationalities, and historical backgrounds focusing on the issues of othering from a postcolonial perspective, this article can serve as a means for its readers to learn more about how the discrimination stemmed from different histories and how cultural background can create similar outcomes.